Fas/CD95-Induced Chemokines Can Serve as "Find-Me" Signals for Apoptotic Cells. - LAVELLE, EDWARD; MARTIN, SEAMUS JOSEPH (My University, 2013)
Apoptosis is commonly thought to represent an immunologically silent or even anti-inflammatory mode of cell death, resulting in cell clearance in the absence of explicit activation of the immune system. However, here we show that Fas/CD95-induced apoptosis is associated with the production of an array of cytokines and chemokines, including IL-6, IL-8, CXCL1, MCP-1, and GMCSF. Fas-induced production of MCP-1 and IL-8 promoted chemotaxis of phagocytes toward apoptotic cells, suggesting that these factors serve as ``find-me?? signals in this context. We also show that RIPK1 and IAPs are required for optimal production of cytokines and chemokines in response to Fas receptor stimulation. Consequently, a synthetic IAP antagonist potently suppressed Fas-dependent expression of multiple proinflammatory mediators and inhibited Fas- induced chemotaxis. Thus, in addition to provoking apoptosis, Fas receptor stimulation can trigger the secretion of chemotactic factors and other immuno- logically active proteins that can influence immune responsiveness toward dying cells
PUBLISHED
Keywords: Apoptosis; Apoptosis